Seismic Test Study on Scale Model of High Temperature Reactor Core Supporting Structure - WANG Dexin;WANG Hongtao;SHI Li;SUN Libin (Yuanzineng kexue jishu, 2023)
The high temperature gas-cooled reactor is one of the six types of the fourth-generation reactors recognized by the international nuclear energy community. It is a new reactor type supported by China’s major scientific and technological projects. The graphite core supporting structure is a discrete structure, and its structural dynamic response under seismic load is quite different from that of continuous structure, showing strong nonlinear and discrete characteristics of structural dynamics. Based on the seismic research of HTR-PM, this work designed and conducted a 1∶4 overall model seismic test of the HTR-PM graphite core supporting structure, and evaluated the seismic performance of the HTR-PM graphite core structure. In the seismic test of the 1∶4 overall model, the boundary conditions such as the graphite core structure and its external supporting were simulated and simplified as close to the actual core as possible. According to the experience of several previous seismic tests, this test also made some optimizations in the measurement of model acceleration, and improved the sampling frequency of the acceleration sensor. According to on-site observation, the control rod can fall smoothly under strong earthquake, which proves that its design strength is sufficient to cope with seismic excitation. When the model is dismantled, all graphite bricks remain structurally intact, and none of the graphite tenon-bonds are damaged. The bearing parts have obvious compression marks which are subjected to repeated alternating loads under seismic loads, but do not break, which prove that the design strength is sufficient to cope with seismic excitation. The Seismosignal software was used to process the test data, and the seismic performance of the graphite core was systematically studied. The dynamic characteristic data measured during the seismic test were analyzed, and the variation laws of the acceleration and displacement of the model were obtained: The acceleration value of the model increases with the height of the model; the higher the position of the brick, the larger the response amplitude; combined with the specific displacement data, it can be proved that both the T-direction and R-direction displacement values belong to the normal range, that is, it meets the requirements of the normal drop of the control rod. After studying various dynamic response characteristics and their distribution laws of the structure, it is concluded that the design of the high temperature gas-cooled reactor core supporting structure can meet the seismic design requirements.